Effects of imperfect CSIS on decode – and - forward relaying under physical layer security - Pham , Ngoc Son (Journal of Technical Education Science, 2016)
Previous works on cooperative communication protocols under physical layer security have only considered perfect channel state information (CSI). In practice, fading channel coefficients are estimated imperfectly at receivers. In this paper, I propose and analyze a cooperative communication scheme under physical layer security with imperfect CSI. In this scheme, a source node transmits secure data to a destination node D with a help of a relay node against an eavesdropper node without direct links of source-destination and source-eavesdropper. The secrecy performance of the proposed scheme is presented by the secrecy outage probability in the closed-form expression. Simulation and analysis results demonstrate that the proposed secrecy scheme is more effective when the channel estimation error at the destination node is smaller than that at the eavesdropper node, and when the distance of the wiretapping link increases. In addition, the analysis values of the secrecy outage probability matches well with the simulation results.